2011
DOI: 10.1002/pi.3179
|View full text |Cite
|
Sign up to set email alerts
|

Aniline oligomers versus polyaniline

Abstract: This paper deals with aniline oligomers produced by the oxidation of aniline with ammonium peroxydisulfate under alkaline conditions. Oligomers obtained in 1 mol L −1 ammonium hydroxide as microspheres have been analyzed. They are brown, non-conducting, and are composed of tens of aniline constitutional units. They contain oxygen in semiquinonoid and quinonoid constitutional units or both, and sulfur in sulfonic or sulfate groups. Phenazine-like units in the oligomers have been identified by UV-visible spectra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
163
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(177 citation statements)
references
References 133 publications
(301 reference statements)
13
163
0
1
Order By: Relevance
“…A prominent band at 824 cm À1 in the substitution region 900-650 cm À1 in the spectrum of the PANI base is due to the C-H out-of-plane bending vibrations of dominating para-coupled constitutional units. The bands at 746 and 691 cm À1 correspond to the C-H out-of-plane bending and out-of-plane ring deformations of a mono-substituted phenylene ring, respectively [24,36]. The spectrum of the oligomers displays bands at 3440 and 3324 cm À1 of asymmetric and symmetric free N-H stretching vibrations, supporting the contribution of the N-H scissoring vibration.…”
Section: Ftir Spectramentioning
confidence: 92%
See 3 more Smart Citations
“…A prominent band at 824 cm À1 in the substitution region 900-650 cm À1 in the spectrum of the PANI base is due to the C-H out-of-plane bending vibrations of dominating para-coupled constitutional units. The bands at 746 and 691 cm À1 correspond to the C-H out-of-plane bending and out-of-plane ring deformations of a mono-substituted phenylene ring, respectively [24,36]. The spectrum of the oligomers displays bands at 3440 and 3324 cm À1 of asymmetric and symmetric free N-H stretching vibrations, supporting the contribution of the N-H scissoring vibration.…”
Section: Ftir Spectramentioning
confidence: 92%
“…The peaks at 3266 and 3195 cm À1 corresponding to the hydrogen-bonded N-H vibrations are detected in the spectrum of aniline oligomers. They are connected with hydrogen bonding of N-H groups with sulfonic or carbonyl groups [24]. The infrared spectra of samples prepared in 0.1 M NH 4 OH and in water display a broad absorption band at wavenumbers higher than 2000 cm À1 , an increased absorption of the bands at 1300 and 1238 cm À1 , and a broad band centred at 1144 cm À1 , which are characteristic of the conducting protonated form of polyaniline [36].…”
Section: Ftir Spectramentioning
confidence: 98%
See 2 more Smart Citations
“…68 However, studies have shown the ability of modulate the inflammatory responses in human fibroblast, 70 since, amino groups can be protonated and in the presence of proton ions that are released in the inflammatory area, resulting in a analgesic effect. 72 It is an electroactive compound, with photoelectrocatalityc degradation 73 . The unshared electron pair on the aniline is delocalized and therefore less available to donate.…”
Section: Chitosan and Anilinementioning
confidence: 99%